Relationship between Teachers' Self-Reported Implementation of Innovative Teaching Methods and their Perceptions of Student Academic Performance in 3D geometry in Public Day Secondary Schools in Musanze District, Rwanda - Emmanuel Byiringiro; Catherine Muhonja Aurah; Beatrice Nakhanu Shikuku (International Journal of Modern Statistics, 2026)
Purpose: This study examined the relationship between teachers’ self-reported implementation of innovative teaching methods and their perceptions of student academic performance in three-dimensional (3D) geometry in public day secondary schools in Musanze District, Rwanda. The study focused on determining whether greater implementation of innovative instructional practices was associated with more favorable teacher perceptions of students’ academic performance in 3D geometry. Methodology: The study employed a quantitative research approach and a correlational research design. The study involved 50 mathematics teachers from six selected public day secondary schools in Musanze District using a census approach. Data were collected using the Teachers’ Instructional Practices and Perceptions Questionnaire (TIPPQ), which measured teachers’ implementation of innovative teaching methods and their perceptions of student academic performance in 3D geometry. Data were analyzed using descriptive statistics and Pearson Product-Moment Correlation Analysis. Findings: The findings revealed a strong, positive, and statistically significant relationship between teachers’ self-reported implementation of innovative teaching methods and their perceptions of student academic performance in 3D geometry, r(48) = .748, p < .001. The coefficient of determination showed that approximately 56.0% of the variance in teachers’ perceptions of student academic performance was associated with the implementation of innovative teaching methods. The results indicate that teachers who reported greater implementation of inquiry-based learning, guided discovery, collaborative learning, and technology-supported instruction also reported more favorable perceptions of students’ performance in 3D geometry. Unique Contribution to Theory, Practice and Policy: The study contributes contextual evidence to Constructivist Learning Theory and the Technological Pedagogical Content Knowledge (TPACK) Framework by demonstrating the relevance of innovative, learner-centered, and technology-supported instructional practices in 3D geometry. In practice, mathematics teachers should strengthen the consistent use of inquiry-based learning, guided discovery, collaborative activities, and digital visualization tools such as GeoGebra and SketchUp. School leaders and education policymakers should provide appropriate instructional resources and targeted professional development to support teachers in effectively implementing innovative methods for 3D geometry instruction.